What role conceptions do multi-healthcare professionals have of physicians and what role expectation do they have of physicians in a community? - Junji Haruta (BMC, 2021)
Abstract Background To create an effective community-based integrated care system, interprofessional collaboration based on healthcare professionals’ mutual understanding of their respective roles must be promoted. This study aimed to identify the role conception and role expectation that other healthcare professionals have towards physicians in the context of a community-based integrated care system. Methods We organized focus groups and adopted ‘Role Theory’ as a theoretical framework. We collected data from healthcare professionals attending a conference on community-based integrated care systems in Japan. Fifty-four non-physician healthcare professionals consented to participate in 7 focus groups. Theme analysis based on the verbatim recorded transcripts was conducted in accordance with the framework of “Role Theory”. Results The role conception of physicians is as a figure of intellectual authority positioned at the top of a traditional hierarchy, with a personal character of criticism/autonomy/closedness, not accommodative of interference from others, and upholding the Biomedical Model as an absolute standard. In response to this, the role expectation of physicians in the community is that they undertake actions that only physicians can undertake to ensure that a flat organization functions properly in providing medical explanations during patient transitions, and to offer healthcare support for patients who are difficult to access. This role expectation also includes the perception of patients as human beings, with physicians adapting to the Bio-Psycho-Social Model, explaining to patients about their disease as an authoritative voice based on an understanding of psychosocial circumstances, and sharing the prognosis of disease or disability. The expected personal character is a person with an open mind who allows others to seek advice, as well as a sense of approachableness which facilitates such seeking of advice. Conclusion In the context of a community-based integrated care system, physicians should consider the understanding of their role conception and role expectation that other professionals have of them, and endeavor to create an open relationship with all healthcare professionals while giving careful consideration to their own role.